A new simple equation for the prediction of filter expansion during backwashing - AKGİRAY, ÖMER (IWA PUBLISHING, 2009)
Fluidization experiments have been carried out with glass spheres, plastic spheres and several sieved fractions of silica sand, garnet sand, perlite and crushed glass. The effect of particle shape on expansion behavior is investigated. Sphericity as determined using the Ergun equation and fixed-bed head loss data is employed to quantify the shape effect. It is found that the influence of particle shape depends on the Reynolds number based on backwash velocity. A new equation that accounts for particle shape is proposed. For the materials studied, the proposed equation gives excellent agreement with both the spherical and the non-spherical particle data.
Keywords: backwash; filter media; fluidization; particle shape; sphericity; water treatment; SOLID-LIQUID SYSTEMS; FLUIDIZATION; VOIDAGE; MEDIA